REPRESENTATIONS OF THE STORY IN CONTEMPORARY SYRIAN SCULPTURE - Mohammed Tahseen Jamal Jalal Alhashimi; Prof Dr. Aqeel Hussein Jasim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this paper is to identify representations of the story in contemporary Syrian sculpture. The researchers took temporal boundaries, where the current research determined the works of Syrian artists in the time period (2018-2019), and the spatial boundaries were the sculpture works that were completed in Syria. The original community of the research is determined by (15) sculptural works executed by Syrian artists that carried the concept of the story and are compatible with the current research (representations of the story in contemporary Syrian sculpture). features of the tale in its implementation. The researcher relied on the descriptive research method to analyze the current research sample because of its characteristics that are commensurate with the nature and objective of the research topic. As for the research sample, the researchers identified the research sample with (3) artistic works, as they were chosen in an intentional way, and in accordance with the research goal according to the following justifications: That the sculptural work has a distinctive contemporary style and differs from the rest of society. Contemporary artworks that bear representations of the story. After the researcher completed his study, he reached a set of results. It is associated with (the story), and its semantic data is an effective semantic link in contemporary Syrian sculpture, through the sculptor’s interest in listing the details of the story or parts of it in the structure of the sculptural work. The effectiveness of the narrative was also represented in the products of contemporary Syrian sculpture through the intensification of the functional patterns of the idea, event and expression, as well as the structural patterns of shape, line, color and size. In addition to representing the themes of the story, interest in the arts of the ancient civilization and its embodiment in a way that simulates the reality of development and prosperity witnessed by the country. The Syrian artist was also interested in the symbolic tale according to its function in its simple form in the artwork, as in model number one